Development and evaluation of a dual-purpose machine for chopping and crushing forage crops. Issue 4 (April 2023) - El Ghobashy, Hossam; Shaban, Yousry; Okasha, Mahmoud; El-Reheem, Solaf Abd; Abdelgawad, Mohamed; Ibrahim, Rania; Ibrahim, Heba; Abdelmohsen, Khaled; Awad, Mahmoud; Cottb, Mokhtar; Elmeadawy, Mohamed; Fathy, Wael; et al.
Abstract: Reducing reliance on fossil fuels with clean and sustainable alternatives is essential for mitigating climate change and global warming-related environmental concerns. Previous researchers have studied the performance of choppers and crushers as separate units powered by diesel or gasoline engines. Nowadays, an increasing interest in producing Eco-friendly machines that stand out for being dual purposes, cost-effectiveness, and with lengths suitable for feeding ruminants are imperative to achieving economic and sustainable goals. Therefore, this study aims to solve these issues and gaps by developing and evaluating a dual-purpose forage machine for chopping and crushing operations to achieve both operations more efficiently and at a lower cost. The developed forage machine's performance was evaluated for chopping operation using maize stalks with four different rotational speeds of 1200, 1400, 1600, and 1800 rpm and four different moisture contents of 22.7, 43.3, 59.8, and 74.6% (w.b.). Also, the crushing operation was evaluated using maize ears with four different crusher speeds of 1200, 1400, 1600, and 1800 rpm and three different sieves with holes' diameters of 6, 8, and 10 mm. The results concluded that the highest efficiencies with values of 94.17 and 92.85% were obtained at 1800 rpm chopper rotational speed and 22.7% moisture content for the chopper and 1200 rpm crusher rotational speed and 10 mm sieve hole diameter for the crusher, respectively. At these proper operational parameters, the machine productivity of 2.44 and 0.31 ton.hr −1, the specific energy requirements of 3.22 and 4.50 kW h.ton −1, and the estimated production costs of 23.56 and 121.24 EGP.ton −1 (1.25 and 6.38 USD.ton −1 ) were obtained for chopper and crusher, respectively.